PEMASARAN ONLINE J.A SEAFOOD MELALUI LINKTREE - Rosmeli, Rosmeli; Ekasari, Novita; Friyani, Rita; Nurhayani, Nurhayani; Wiralestari, Wiralestari (Universitas Negeri Surabaya, 2025)
The culinary industry plays a significant role in indonesia's regional gross domestic product (gdp). In 2023, the food and beverage industry contributed 39.10% to the non-oil and gas industrial gdp and 6.55% to the national gdp. J.A. Seafood is one of the culinary msmes located in jambi province. The production process begins with the purchase of fresh raw materials from fishermen's catches, which are then processed into ready-to-eat food and sold to consumers through digital marketing platforms. In running its business, J.A. Seafood already utilizes digital media. J.A. Seafood uses instagram, whatsapp, grabfood, gofood, shopeefood, and maximfood as its marketing channels. The business has a total of 6,070 followers. This large following presents an opportunity for J.A. Seafood to further expand its business. The objectives of the community service project for the partner business are: (1) to facilitate easier marketing for the partner by integrating all business channels into one link through linktree. The outcome of the community service project is that the partner business (J.A. Seafood) now has a linktree link displayed on its instagram account, making it easier for consumers to make purchases. The use of linktree also provides more convenient access for consumers through a single link. For the partner business, the use of linktree increases accessibility, allowing the partner to reach more customers across various platforms, ultimately leading to increased sales.